(untitled) (The Eurasia Proceedings of Educational and Social Sciences, 2019)
During the last decade, the importance of leaving a rational paradigm, debtor of functionalist and utilitarian models, towards another more congruent with the preservation of natural resources, and therefore of life, has been widely discussed. In the same way, different voices have been raised, pointing out the urgency of inserting these precepts into the educational field, hoping to achieve the true cultural transformation that is needed to consolidate the change. Multiple International Entities promote sustainability in Education as an initiative that should be ambitious, complex and reforming character, given the global scope of the social, economic and environmental situation affecting the planet. Through the exploration of the relationship between education, cultural change and sustainability, this work presents an overview of the educational situation in terms of its collaboration towards sustainable development from a critical vision of the objectives, foundations, challenges of environmental education and improvement opportunities; the aspects that positively impact on conceptual development and educational practice are argued, as well as the way in which new approaches of raising environmental problems and working towards a more sustainable future could be generated. Finally, certain proposed solutions are suggested.